IMPACTS OF GENDER-BASED VIOLENCE ON CHILDREN’S DEVELOPMENT IN GOBACHOP COMMUNITY, PAYNESVILLE, MONTSERRADO COUNTY, LIBERIA - Anyikwa, Ngozi E.; Taydor, Gbeinlehguan Melvin (Journal of Early Childhood and Primary Education, 2025)
Gender-based violence is grounded in unequal power relations, cultural norms, and discriminatory practices that privilege one gender over another. This study investigated the impact of gender-based violence (GBV) on children’s development in Gobachop Community, Paynesville, Montserrado County, Liberia. Two research questions and two hypotheses guided the study. Descriptive survey research design was employed. The population of the study comprised of 60 children in Paynesville, Montserrado County, Liberia.  There was no sampling because the population was manageable for the study. A Five-point rating scale questionnaire titled “Questionnaire on the Impact of Gender-Based Violence (QIGBV)” was used for data collection. An overall Cronbach alpha co-efficient of 0.74 was used to establish the reliability of the study.  The instrument was validated by three experts, one form measurement and evaluation unit in the Department of Educational Foundations, one from the Department of Early Childhood and Primary Education, and one from the Rudolph Kwanue University, Republic of Liberia. Mean and standard deviation were used to answer the research questions while t-test was used to test null hypotheses at 0.05 level of significance.The finding of the study among others showed that the impacts of gender-based violence on the physical and social development of children leads to injuries, children perceiving and reacting to things negatively, and most often young men sometimes involving into criminal offences against the abusive parent (mostly fathers), in order to protect their mother and siblings, as well as regularly become victims of an act of revenge by the abuser against the mother in Gobachop Community. Recommendations include establishment of support Systems, community awareness programs, capacity building for caregivers, policy implementation and enforcement, access to education, mental health services, economic empowerment, collaboration and partnerships among government agencies, NGOs, community-based organizations, and other stakeholders to ensure a coordinated response to GBV and its impact on children development.
Keywords: Gender-based Violence; Impact; Physical Impact; Social Impact; Development